محددات تدفق الاستثمارات الأجنبية المباشرة في كل من الجزائر، تونس والمغرب " دراسة قياسية مقارنة خلال الفترة 1996-2012 - زرقين, عبود; بيري, نورة (جامعة الوادي University of Eloued, 2014)
تهدف هذه الدراسة إلى التعرف على المحددات الرئيسية لتدفق الاستثمارات الأجنبية المباشرة في كل من الجزائر، تونس والمغرب خلال الفترة 1996-2012. وبعد مراجعة الأدبيات المتعلقة بالمحددات النظرية للاستثمار الأجنبي المباشر في الدول المضيفة، تم إعداد نموذج لقياس العوامل المؤثرة على تدفقات الاستثمارات الأجنبية المباشرة داخل كل من الجزائر، تونس والمغرب، على النحو المحدد في الأدبيات الاقتصادية والدراسات السابقة ذات الصلة. وذلك للاستفادة من هذا النموذج في التعرف على أهم السياسات التي تساعد على جذب الاستثمارات الأجنبية المباشرة لدول الدراسة. وقد توصلت الدراسة إلى أن كل من العوامل المحلية كالناتج المحلي الإجمالي وتطور القطاع المالي وسعر الصرف من أكثر العوامل تأثيرا على تدفقات ا الاستثمارات الأجنبية المباشر في كل من الجزائر، تونس والمغرب This study aims to identify the key determinants of the flow of foreign direct investments in Algeria, Tunisia and Morocco during the period 1996-2012. After reviewing the literature on the theoretical determinants of foreign direct investment in the host countries , have been prepared in a form to measure the factors affecting foreign direct investment flows within each from Algeria , Morocco and Tunisia , as specified in the economic literature and previous studies relevant . So take advantage of this model to identify the most important policies that help to attract foreign direct investment to countries study. Study has come to all of the local factors such as GDP and the evolution of the financial sector and the exchange rate of the most influential factors on the flows of foreign investment direct in Algeria, Tunisia and Morocco
Determinants of foreign direct investments flow to Algeria, Tunisia and Morocco A comparative econometric study during the period 1996-2012
مقال- مجلة رؤى اقتصادية
Keywords: الاستثمار الأجنبي المباشر ، مناخ الاستثمار ، مؤشرات الأداء، التنمية الاقتصادية ، حجم السوق: foreign direct investment , the investment climate , performance indicators , economic development , the size of the market. (JEL) Classification : C01, F21, F23